Contemporary research methods in pharmacy and health services - Desselle, Shane P.; Garcia-Cardenas, Victoria; Anderson, Claire, PhD; Aslani, Parisa; Chen, Aleda M.H; Chen, T. (Timothy) (Academic Press, an imprint of Elsevier, 2022)
Emerging methods, as well as best practices in well-used methods, in pharmacy are of great benefit to researchers, graduate students, graduate programs, residents and fellows also in other health science areas. Researchers require a text to assist in the design of experiments to address seemingly age-old problems. New interventions are needed to improve medication adherence, patients' lived experiences in health care, provider-patient relationships, and even various facets of pharmacogenomics. Advances in systems re-engineering can optimize health care practitioners' roles. Contemporary Research Methods in Pharmacy and Health Services includes multi-authored chapters by renowned experts in their field. Chapters cover examples in pharmacy, health services and others transcendent of medical care, following a standardized format, including key research points; valid and invalid assumptions; pitfalls to avoid; applications; and further inquiry. This is a valuable resource for researchers both in academia and corporate R&D, primarily in pharmacy but also in health services, and other health disciplines. Social science researchers and government scientists can also benefit from the reading.